Kubord-fasttext - Aftonbladet 2010–2022 - token - Språkbanken Text (University of Gothenburg, 2024)
Kubord-fasttext is a collection of fasttext models, developed within a collaboration between
KBLab and Språkbanken Text, that have
been trained on the same underlying data as Kubord 2.
The models have been trained on the token and the lemma level. The tool that has been used for the training is
Gensim, with the following parameter settings:
min_n 4, max_n 7, 20 epoker, dim 300, and lr .05.

Kubord-fasttext är en samling fasttext-modeller, framtagna inom ett samarbete mellan
KB-labb och Språkbanken Text, som tränats på
samma underliggande data som Kubord 2. Modellerna är
tränade på token- och lemmanivå. Verktyget som använts vid träning är
Gensim, med följande parameterinställningar:
min_n 4, max_n 7, 20 epoker, dim 300 och lr .05.
Kubord-fasttext - Aftonbladet 2010–2022 - token
Keywords: Language Technology (Computational Linguistics); model; Natural Language Processing; Språkbehandling och datorlingvistik